Phytohormone inhibitor treatments phenocopy brassinosteroid–gibberellin dwarf mutant interactions in maize - Best, Norman B. (Plant Direct, 2017)
Phytohormone biosynthesis produces metabolites with profound effects on plant growth and development. Modulation of hormone levels during developmental events, in response to the environment, by genetic polymorphism, or by chemical application, can reveal the plant processes most responsive to a phytohormone. Applications of chemical inhibitors and subsequent measurements of specific phytohormones can determine whether, and which, phytohormone is affected by a molecule. In many cases, the sensitivity of biochemical testing has determined multiple pathways affected by a single inhibitor. Genetic studies are not subject to this problem, and a wealth of data about the morphological impacts of hormone biosynthetic inhibition have accumulated through the study of enzyme mutants. In this work, we sought to assess the specificity of three triazole inhibitors of cytochrome P450s by determining their abilities to recapitulate the phenotypes of single and double mutants affected in the production of brassinosteroid (BR) and gibberellin (GA) biosynthesis. The GA biosynthetic inhibitors uniconazole (UCZ) and paclobutrazol (PAC) were applied to the BR biosynthetic mutant nana plant2 (na2), and all double‐mutant phenotypes were recovered in the UCZ treatment. PAC was unable to suppress the retention of pistils in the tassels of na2 mutant plants. The BR biosynthetic inhibitor propiconazole (PCZ) suppressed tiller outgrowth in the GA biosynthetic mutant dwarf5 (d5). All treatments were additive with genetic mutants for effects on plant height. Due to additional measurements performed here but not in previous studies of the double mutants, we detected new interactions between GA and BR biosynthesis affecting the days to tassel emergence and tassel branching. These experiments, a refinement of our previous model, and a discussion of the extension of this type of work are presented.